Spatial and Temporal Drought Evaluation Based on Water Balance Using TerraClimate Data in East Java Province - Nizar Manarul Hidayat; Sulistiani Sulistiani (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2026)
Drought is one of the most critical hydrometeorological hazards affecting water resources and agricultural sustainability in East Java, Indonesia. This study evaluates the spatial and temporal characteristics of drought using a water balance approach based on TerraClimate data from 1981–2017 and validates the results against rainfall observations from 14 stations during 2008–2017. Groundwater availability (GWA) was estimated using the Thornthwaite–Mather water balance method by integrating monthly precipitation and potential evapotranspiration (PET), with adjustments for local soil properties derived from FAO soil classifications. Trend analysis using the Mann–Kendall test and Sen’s slope revealed a significant increase in dry-month frequency across East Java, particularly in northern coastal and eastern regions, with trends ranging from 0.2 to 0.4 additional dry months per decade. Validation results demonstrated strong agreement between TerraClimate and observational data, with correlation coefficients ranging from 0.76 to 0.997 and RMSE values between 4.78 and 85.3 mm. Higher model performance was observed in inland and highland areas, while larger discrepancies occurred in coastal regions due to greater microclimatic variability. Seasonal analysis showed that drought conditions mainly occur from May to September, whereas water surplus periods dominate from October to March. Spatially, drought propagation was observed from northern coastal areas toward inland regions of central East Java. The findings demonstrate the reliability of TerraClimate for regional drought monitoring and support its application in early warning systems, adaptive cropping calendar management, and the development of small-scale water storage infrastructure in drought-prone areas.